The Use Of Alternative Stain In Rose Bengal Test Antigen Preparation Which Specific For Brucellosis.: Erada A .J . Saeed , Sahar A. Al_Bayatti - Saeed, Erada A .J . (The Iraqi Journal of Veterinary Medicine, 2006)
The Rose Bengal test is one of the famous diagnostic test of Brucellosisspecially as a screening test in order to detect the infection in limited area.Rose Bengal standard stain which producd by specific companies was used inpreparation of the test special antigen , The stain gives the known pink colourfor the antigen during the test that make the agglutination in positive cases morevisible due to the reaction between antigen and the specific antibodies ofBrucella which found in the serum sample of human and different animals.Antigen for the Rose Bengal test in this study is prepared by using alternativestain easily found in local supermarkets using for food colours and notexpensive like standard stain. All standard tests were down for the stain like thecolour ,pH, stability are same for two stains until the date of expire of antigen.The antigen prepared with alternative stain was used in comparative with theantigen prepared with standard stain for testing serum samples of human anddifferent animals, the results deal no significant different statistically betweenthem that means as a result we can prepare antigen more easily and notexpensive.